Whole-Genome Sequence Datasets: A Powerful Resource for the Food Microbiology Laboratory Toolbox - Carrillo, Catherine D.; Blais, Burton W. (Frontiers in Sustainable Food Systems, 2021)
Whole-genome sequencing (WGS) technologies are rapidly being adopted for routine use in food microbiology laboratories worldwide. Examples of how WGS is used to support food safety testing include gene marker discovery (e.g., virulence and anti-microbial resistance gene determination) and high-resolution typing (e.g., cg/wgMLST analysis). This has led to the establishment of large WGS databases representing the genomes of thousands of different types of food pathogenic and commensal bacteria. This information constitutes an invaluable resource that can be leveraged to develop and validate routine test methods used to support regulatory and industry food safety objectives. For example, well-curated raw and assembled genomic datasets of the key food pathogens (Salmonella enterica, Listeria monocytogenes, and Shiga-toxigenic Escherichia coli) have been used in our laboratory in studies to validate bioinformatics pipelines, as well as new molecular methods as a prelude to the laboratory phase of the “wet lab” validation process. The application of genomic information to food microbiology method development will decrease the cost of test development and lead to the generation of more robust methodologies supporting risk assessment and risk management actions.